Bhutan : Assessment Letter for the World Bank. (Policy Papers; Policy Paper, 2012)
Bhutan's growth has remained robust, but the current account deficit has widened. -- Bhutan's economy has expanded at a robust pace driven by the hydropower sector developments. GDP growth is estimated at nearly 8 percent in 2011/12 (from 8.5 percent in 2010/11), and is projected to reach 12.5 percent in 2012/13 due to the acceleration in hydropower-related construction. Inflation has risen, reaching 13.5 percent in 2012Q2, with both food and nonfood components accelerating. Bhutan's medium-term outlook is favorable, as growth should remain strong at around 8-9 percent over the medium term, driven by developments in the hydropower sector, manufacturing, and domestic services.